Export management and incomplete VAT rebates to exporters: the case of China - Sandra Poncet; Julien Gourdon; Laura Hering; Stéphanie Monjon (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Compared to most countries, China's value-added tax (VAT) system is not neutral and makes it less advantageous to export a product than to sell it domestically, as exporters may not receive a complete refund on the domestic VAT they have paid on their inputs. However, the large and frequent changes to the VAT refunds which are offered to exporters have been led China to be accused of providing its firms with an unfair advantage in global trade. We use city-specific export-quantity data at the HS6-product level over the 2003-12 period to assess how changes in these VAT rebates have affected Chinese export performance. Our identification strategy relies on triple difference estimates that exploit an eligibility rule which disqualifies processing trade with supplied materials from these rebates. We find that changes in VAT rebates have significant export repercussions: eligible export quantity for a given city-HS6 pair rises by 6.5% following a one percentage-point increase in the VAT rebate. This magnitude yields a better understanding of the strong resistance of Chinese exports during the global recession, in which export rebates increased substantially.
Keywords: F10; F14; O14; 330